Impactos socioambientais e econômicos da usina hidrelétrica de Marabá-PA (2014-2016) na Comunidade da Ilha de São Vicente-TO. - Cruz, Gercina Rodrigues da (2017)
The socio-environmental impacts, the territorial transformations in the way of life, the production of the traditional communities, since the implantation of the great works of hydropower plants cause compulsory displacement, and are provoking worldwide discussions in the academic, political and social spheres. The conceptions of the processes that legitimize the energy policy in the Amazon are underpinned by the territorialization of "traditional communities" – wild slaves - for socio-environmental processes and specific territorialities. The pertinence of this research is to give visibility to the contexts of struggles, resistance and the argumentation to mitigate the impacts that will occur in the community "Ilha de São Vicente-TO", processes of territorialization that correspond to them for confrontations in the public hearings. In understanding these issues, the use, occupation and plundering of the natural resources of the Amazon region require the understanding of the dialectic of borders in the energy production, in this case, the Marabá-PA hydroelectric plant, as well as the constraints to the territorialization process, consequences of large investments and infrastructure works. The methodology used was based on analytical research with qualitative approaches, in locu observation and semi-structured interviews. Thus the dimension that the large hydroelectric projects reach potentially rich and densely populated areas, it becomes indispensable to increase the theoretical/methodological and empirical research, the apprehension of the interests of the entrepreneur in the space/territory, and the impacts that will occur in the way of life and in the representation of wild slaves communities